Respuesta :
Answer:
Step-by-step explanation:
Replace g(x) with y, then switch the x and y variables:
[tex]x=\frac{-5y+5}{2}[/tex]
Solve for the new y value, multiply by 2:
[tex]2x=-5y+5[/tex]
Subtract 5 on both sides:
[tex]2x-5=-5y[/tex]
Divide by -5 on both sides:
[tex]-\frac{2x-5}{5} =y[/tex]
Distribute the negative sign and rearrange:
[tex]\frac{-2x+5}{5} =\frac{5-2x}{5} =g^-^1(x)[/tex]
Answer:
- A. g⁻¹(x) = (5 - 2x)/5
Step-by-step explanation:
Given function
- g(x) = (-5x + 5)/2
Find
- the inverse of g(x)
Solution
Substitute x with y and g(x) with x and then solve for y:
- x = (-5y + 5) /2
- 2x = -5y + 5
- 5y = -2x + 5
- y = (-2x + 5)/5
- y = (5 - 2x)/5
Replace y with g⁻¹(x)
- g⁻¹(x) = (5 - 2x)/5
Correct choice is A